Fundamental of Entrepreneurship ENT300 : Magnus Fish / Charles Arnold Kajan ... [et al.] - Kajan, Charles Arnold; Remil, Lennon Dungau; Chimi, Julis Pawi; Mohd Zainal, Zainazrul Farhan (Research Management Institute (RMI), Universiti Teknologi MARA, 2016)
The business plan of MAGNUS FISH is prcposed so that it can be undertaken comprehensive manner. This business plan led us toward opportunity to access the business in the future. We decided to make a partnership in this business which we supply fresh water fish in the premises, and we also supply it to wet market. This business consists of four shareholders.